POTENSI DAN ANALISA BIAYA PENYEDIAAN BIBIT TEBU (Saccharum officinarum L.) UNGGUL SECARA IN VITRO DI PT. GUNUNG MADU PLANTATIONS - Heni Erlita Sari; Mahfut Mahfut; Alhuda Niftakul Ahyar (Universitas Islam Negeri Sumatera Utara, 2022)
Sugarcane productivity included cane yield and sugar extracted rate (rendemen) fluctuated annually. The main causes of low sugarcane productivity is quality of planting material with no high sugar extracted rate (sugar rendemen) potential, resistance to pests and diseases, stability production, tolerance to climate changed and early age of harvest. For increasing of the yield productivity and producing a superior sugarcane planting material with competitiveness cost, the vegetative propagation through in vitro culture technique via shoot tip culture was carried out. The objective of this research is to produce a superior sugarcane planting in vitro and analyze the costs required. The research was carried out at the Tissue Culture Laboratory, PT. Gunung Madu Plantations (GMP) in March-May 2021. The research stages started from the preparation of explant source plants, sterilization of explants and tools, manufacture of stock solutions and planting media, subculture, and analysis of the costs needed to provide superior sugarcane seeds. The results showed that the basal swelling of explants, increasing the number of shoots, root elongation, and the method of providing superior sugarcane seeds from apical shoot explants in vitro were relatively more competitive with the price of plantlets per culture tube contained 10 clones costly were Rp. 20,328, compared with conventional propagation methods. with the price of sugar cane seedlings material were Rp 1,603/stem.